Lexical Variability in Ruthenian Translations of the Book Żywoty Świętych by Piotr Skarga: the Life of St Athanasius of Alexandria - Sapozhnikova, Galina (Slavistica Vilnensis, 2024)
In order to clarify the textual history of manuscript copies of the Ruthenian Life of St Athanasius of Alexandria, translated from Piotr Skarga’s Żywoty Świętych, the article analyses the variety of the most frequent lexemes of the Life using methods of textual criticism. Variants of the seven considered lexemes of each of the 13 manuscript copies of the Life, grouped in tables, show the direction of lexical changes, as well as the interaction between manuscript copies of two different translations of the same Polish original. It is shown that the vocabulary of the manuscript copies Sof. 278, Sof. 279, KPL 370, KPL 371, CAM KDA 674 of the second more widespread translation must have been slightly edited according to the manuscript copy of NTŠ 322 (or a similar textual type) of the first translation. The manuscript copies EPARCH. 460, BN 15628 of the second translation contain traises of secondary interaction with a different type of texts. The data also shows the editing of lexems of the archetype Šept. 31, NTŠ 322 according to the manuscript copie of other translation. The results of the study of lexical variability complement and agree with the results of the analysis of the conflate readings and alternative textual variants found in the manuscript copies of St Athanasius’ Life, according to which additional variants of the text were used in a number of manuscript copies of the Life during the rewriting of the antigraph.